2014
DOI: 10.1111/crj.12143
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Class I and II HLA alleles in patients with lung cancer according to chemotherapy response and 5‐year survival

Abstract: Our results suggested that expressions of HLA-BW6 and HLA-DRB1*13 alleles may be predictable markers for response to chemotherapy in lung cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…And HLA-DRB1*07 was significantly higher in patients at an early stage than those at an advanced stage 37. Omer Araz et al found NSCLC patients who had better response to gemcitabine and cisplatin combination chemotherapy regimen had significantly higher frequency of HLA-DRB1*13, HLA-DQ5, HLA-DQ7 38…”
Section: Encoding Gene Of Mhc Class II and Nsclcmentioning
confidence: 98%
“…And HLA-DRB1*07 was significantly higher in patients at an early stage than those at an advanced stage 37. Omer Araz et al found NSCLC patients who had better response to gemcitabine and cisplatin combination chemotherapy regimen had significantly higher frequency of HLA-DRB1*13, HLA-DQ5, HLA-DQ7 38…”
Section: Encoding Gene Of Mhc Class II and Nsclcmentioning
confidence: 98%
“…Lung cancer is one of the most common malignant tumours in humans, causing many deaths every year [ 80 , 81 ]. The 5-year survival rate of lung cancer patients is still very low despite continuous improvement and progress in the diagnosis and treatment of lung cancer [ 82 , 83 ]. Non-small-cell lung carcinoma (NSCLC) accounts for 85% of all pathological types of lung cancer [ 82 , 83 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 5-year survival rate of lung cancer patients is still very low despite continuous improvement and progress in the diagnosis and treatment of lung cancer [ 82 , 83 ]. Non-small-cell lung carcinoma (NSCLC) accounts for 85% of all pathological types of lung cancer [ 82 , 83 ]. Our attention should be focused on the abnormal molecular biological characteristics of NSCLC to find an effective treatment.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Due to the high metastasis and chemoresistance, the 5-year survival rate of NSCLC patients remains dismal. 5,6 It is urgently needed to identify novel effective early diagnostic markers and therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%